2023
DOI: 10.2166/wpt.2023.035
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent flow mechanisms in meandering channels with sediment transport

Abstract: This research aims to investigate the near-bed turbulent flow characteristics in a meandering channel with both mobile bed and immobile bed conditions. Experiments were performed in a prismatic rectangular meandering channel with a non-uniform sand bed of size d50 = 0.523mm. The three-dimensional instantaneous fluid velocity was collected using the Acoustic Doppler velocimeter which will provide important results related to the flow turbulence such as mean flow velocity, turbulence intensity, Reynolds shear st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In our study, the meandering channel's geometry with successive 180 • and 120 • bends with different angles, and the extended approach channel distinguishes it from other channels studied in the literature, which typically feature more uniform or less extreme bend angles. The experimental model in many studies in the literature consists of only a single bend or narrow-angle uniform sinusoidal bends [1,[4][5][6][7][9][10][11][12]14]. In this study, the fairly long approach channel also ensures the flow reaches fully developed flow conditions before entering the meanders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the meandering channel's geometry with successive 180 • and 120 • bends with different angles, and the extended approach channel distinguishes it from other channels studied in the literature, which typically feature more uniform or less extreme bend angles. The experimental model in many studies in the literature consists of only a single bend or narrow-angle uniform sinusoidal bends [1,[4][5][6][7][9][10][11][12]14]. In this study, the fairly long approach channel also ensures the flow reaches fully developed flow conditions before entering the meanders.…”
Section: Methodsmentioning
confidence: 99%
“…Dombroski and Crimaldi evaluated the accuracy of ADV velocity measurement data in turbulent boundary layer flow over a hydraulically smooth surface [8]. Sahoo and Sharma studied the turbulent flow mechanism in meandering channels using the ADV technique [12]. Laboratory studies performed by Ishigaki et al and Bai et al with PIV can be shown as other example studies for understanding flow behavior in a meandering channel [13,14].…”
Section: Introductionmentioning
confidence: 99%